2007
DOI: 10.1242/jeb.002204
|View full text |Cite
|
Sign up to set email alerts
|

Passive mechanical properties of human gastrocnemius muscle–tendon units, muscle fascicles and tendonsin vivo

Abstract: SUMMARY This study provides the first in vivo measures of the passive length–tension properties of relaxed human muscle fascicles and their tendons. A new method was used to derive passive length–tension properties of human gastrocnemius muscle–tendon units from measures of ankle stiffness obtained at a range of knee angles. Passive length–tension curves of the muscle–tendon unit were then combined with ultrasonographic measures of muscle fascicle length and pennation to determine passive length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 39 publications
7
84
1
5
Order By: Relevance
“…Our estimates of the passive F-L curves of the SOL fascicles were consistently less steep than the theoretical model (Fig.4) and compared to those from other mammalian species (Azizi and Roberts, 2010), despite the peak passive muscle forces and stiffness being commensurate with those reported for the human gastrocnemius muscle (Hoang et al, 2007;Gao et al, 2009) (taking into account muscle cross-sectional area). Our results show that the length at which passive SOL forces begin to develop correspond closely to the predicted L 0 , corroborating both standard models (Zajac, 1989) and previous experimental data (Azizi and Roberts, 2010;Winters et al, 2011), and provides further confidence in our estimates of subject-specific F-L data.…”
Section: Subject-specific Force-length Curvessupporting
confidence: 52%
“…Our estimates of the passive F-L curves of the SOL fascicles were consistently less steep than the theoretical model (Fig.4) and compared to those from other mammalian species (Azizi and Roberts, 2010), despite the peak passive muscle forces and stiffness being commensurate with those reported for the human gastrocnemius muscle (Hoang et al, 2007;Gao et al, 2009) (taking into account muscle cross-sectional area). Our results show that the length at which passive SOL forces begin to develop correspond closely to the predicted L 0 , corroborating both standard models (Zajac, 1989) and previous experimental data (Azizi and Roberts, 2010;Winters et al, 2011), and provides further confidence in our estimates of subject-specific F-L data.…”
Section: Subject-specific Force-length Curvessupporting
confidence: 52%
“…Firstly, the passive muscle stiffness was not measured directly. Hoang et al (2007b) showed that ultrasonography could be used to assess muscle and tendon force-length relationships, and this method has been very useful in determining the plyometric training effects on passive muscle stiffness. Secondly, the tendon stiffness was assessed during an isometric contraction, while MTC stiffness was measured during passive stretching.…”
Section: Introductionmentioning
confidence: 99%
“…Two commonly applied strategies to standardize probe orientation are: (1) a perpendicular orientation of the probe to the skin, 25,32,33,35 and (2) ultrasound visualization of an image with "clearly visible fascicles." 4,13,14,16,19,22,23,25,27,[30][31][32]34,38 However, no systematic experimental evidence seems to be available to validate these strategies. The reason for this is the noninvasiveness of ultrasound, which is generally a major advantage of the method.…”
mentioning
confidence: 99%